Les fonctions démystificatrices de la guerre dans les Âmes grises et Le rapport de Brodeck de Philippe Claudel - ABDELLI, Yacine (Journal of Human Sciences, 2016)
This article entitled "demystifications functions of war in gray souls and the report Brodeckto Philippe Claudel attempts to elucidate one side of the narrative strategy with what is told the theme of war. On the other hand, he tries to describe the impact of the event on the lives of the characters.